Analysis of Rural Poverty in Bengkulu Province Indonesia - Barika, Barika; Gunawan, Romi; Zulyanto, Aan (PT Inovasi Pratama Internasional, 2025)
This study examines poverty in the rural districts of Bengkulu Province. This study investigates how poverty in rural Bengkulu Province is affected by economic growth, village fund allocation, village development index, income distribution disparity, and duration of education. Panel data from 2018 to 2023, covering nine districts in the province, were used in this study. According to the study results, since 2018, village fund distribution and economic growth have been factors that have had a favorable impact on poverty in the rural districts of Bengkulu Province. The village development index, length of schooling, and economic disparity contribute to poverty in the rural districts of Bengkulu Province.